Organic materials as smart nanocarriers for drug delivery - Grumezescu, Alexandru Mihai (Pharmaceutical nanotechnology series., 2018)
"Organic Materials as Smart Nanocarriers for Drug Delivery presents the latest developments in the area of organic frameworks used in pharmaceutical nanotechnology. An up-to-date overview of organic smart nanocarriers is explored, along with the different types of nanocarriers, including polymeric micelles, cyclodextrins, hydrogels, lipid nanoparticles and nanoemlusions. Written by a diverse range of international academics, this book is a valuable reference for researchers in biomaterials, the pharmaceutical industry, and those who want to learn more about the current applications of organic smart nanocarriers. Explores the most recent molecular- and structure-based applications of organic smart nanocarriers in drug deliveryHighlights different smart nanocarriers and assesses their intricate organic structural properties for improving drug deliveryAssesses how molecular organic frameworks lead to more effective drug delivery systems"--